Creating an online information literacy course for concurrent enrollment students: A collaboration with a state-sponsored online school. Issue 1 (2nd January 2017) - Davis, G. Megan; Watson, Elaine
ABSTRACT: This article discusses a collaborative project to create an online one-credit library research course for high school students in a dual credit program. The project included a team of reference and instruction librarians at a midsize public university, the university's concurrent enrollment program, and an online state-sponsored school that provided courses to high school students. Current literature related to the information literacy knowledge gap, outreach to secondary schools, dual credit or concurrent enrollment programs, and for-credit online information literacy courses is reviewed. The process of creating the course will be discussed along with the benefits and challenges of the project.